Avaliação de dor e estresse em leitões submetidos a procedimentos de manejo na criação intensiva de suínos - Cassel, Taciele Gasparetto (2016)
In its first days, piglets frequently are subjected to several raising procedures that aim on preventing health and welfare issues to the piglets an their mothers, like teeth and tail cutting, iron injections to avoid them from harming each other or the females udder, canibalism between animals and anemia prevention, respectively. Some procedures, such as individual branding and castration aim to facilitate management or some of the end user needs like flavor or traceability. But more and more those handling procedures are recognized by groups of end users and animal welfare activists as painful and unnecessary procedures, therefore, the search for more comfortable and alternative procedures for the animals. This study took place in a swine farm in Charrua/RS, it as standardized in a period of time, with a total of 70 piglets, divided in four groups with the same number of males and females, the first group was subjected to iron injection, the second to tail cutting, the third to ear tagging and the fourth to castration, where the animal has been controlled on the physiological and behavioural parameters. Vocalization and intensity peak were measured during the procedures for a four hour period, behaviour was measured by direct observation and blood samples are collected in a specific timetable for the cortisol hormone measurement. Few papers are found in Brazil that approach all these handling procedures together and how it affects in stress in such young animals, this reinforces the need of less traumatic and more comfortable alternative handling procedures. This study aims to measure pain and stress levels, using behaviour and physiological parameters, that routine handling procedures in intensive swine farming induce, because the animals are subjected to several procedures in sequence in a brief period of existence, this implicates in the need of handling procedures that regard animal welfare in swine farming, besides the animal comfort, it will be profitable. However, the only group that met a positive correlation between vocalization levels and a raise in cortisol levels was the fourth group, agreeing that among the other procedures, castration was the most invasive and painful, because it involves testicle extraction and tissue scarring, like other papers already found. The second group, exposed to tail docking procedure, presented a significant raise on cortisol levels on males after four hours that was already established, instead of what growers claim, the procedure that causes acute pain and can lead to neuroma formation but, there is no data supporting sensibility difference between genders. All groups presented raises on cortisol levels in the first moment, that can be explained by the acute stress by the handling and gathering for the first blood sample and first human contact but, the animal circadian cycle for the fact of swine are matutinal animals, higher levels of cortisol are expected in the morning. Behavioural evaluation, look out after all four procedures, every animal kept themselves isolated from the litter for the first hour, after that they searched for the mother to feed, this data was found in other papers corroborating that all procedures are capable of inducing stress and acute pain, that may become chronic, inducing behaviour alterations in piglets like avoiding other animals and moving around. It was proven that all procedures cause pain at the moment of the handling cause acute pain, prejudice to the locomotion and the living with the group and after the procedure it can remaining for at least four hours. In modern swine farming it becomes of interest the search for new technologies and procedures that regard animal welfare and minimize discomfort provoked by these handling procedures that some were proven to be unnecessary but still are routine procedures in swine farming.